2023
DOI: 10.3389/fmicb.2023.1093668
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a lytic Pseudomonas aeruginosa phage vB_PaeP_ASP23 and functional analysis of its lysin LysASP and holin HolASP

Abstract: In this study, we isolated a lytic Pseudomonas aeruginosa phage (vB_PaeP_ASP23) from the sewage of a mink farm, characterized its complete genome and analyzed the function of its putative lysin and holin. Morphological characterization and genome annotation showed that phage ASP23 belonged to the Krylovirinae family genus Phikmvvirus, and it had a latent period of 10 min and a burst size of 140 pfu/infected cell. In minks challenged with P. aeruginosa, phage ASP23 significantly reduced bacterial counts in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, compared to the 63.6% (21/33) lysis rate of phage Lx18, the two phages isolated in this study showed a narrower host range ( Yin et al, 2022 ). In addition, phage ASP23 exhibited a lysis rate of 68% against clinically isolated strains of P. aeruginosa ( Cui et al, 2023 ). When phages infect bacteria, the main structures involved in binding to the host bacterial surface receptors are the phage receptor binding proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared to the 63.6% (21/33) lysis rate of phage Lx18, the two phages isolated in this study showed a narrower host range ( Yin et al, 2022 ). In addition, phage ASP23 exhibited a lysis rate of 68% against clinically isolated strains of P. aeruginosa ( Cui et al, 2023 ). When phages infect bacteria, the main structures involved in binding to the host bacterial surface receptors are the phage receptor binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…With the emergence of multidrug-resistant bacteria, phage cocktails composed of multiple phage strains have become a preferred method to improve the efficiency and effectiveness of antibacterial treatment ( Petsong et al, 2019 ). Some research groups have reported the feasibility of phage therapy for P. aeruginosa infections in animals ( Shi et al, 2020 ; Yin et al, 2022 ; Cui et al, 2023 ). However, according to our literature review, Cao et al (2015) and Gu et al (2016) extensively investigated and evaluated the therapeutic efficacy of nebulized or nasal-drip bacteriophages in a mink model of hemorrhagic pneumonia caused by P. aeruginosa .…”
Section: Introductionmentioning
confidence: 99%